HUBUNGAN PERILAKU ORANG TUA DENGAN KEJADIAN DIARE PADA BALITA DI PUSKESMAS REJOSARI KOTA PEKANBARU TAHUN 2018 - PENTI DORA YANTI; Afritayeni Afritayeni; Nur Fani Amanda (Institut Kesehatan dan Teknologi Al Insyirah, 2019)
ABSTRAK According to the World Health Organization (WHO), diarrhea is the cause of death by as much as 4% of all deaths and 5% of worldwide morbidity, about 2.2 million people worldwide diarrhea, the largest population occurs in toddlers, especially in developing countries. Based on data from Pekanbaru City Health Office, Rejosari Community Health Center is the highest health center for diarrhea case in under fives. The purpose of this study to determine the relationship of parental behavior with the incidence of diarrhea in infants. The research design used is quantitative analytic. The population of this research is parents who bring their children to Rejosari health center which is 220 people. The sample technique used is accidental sampling, which is 142 people. Data collection techniques used are primary data by distributing questionnaires and processed in univariate and bivariate. The result of univariate analysis showed that most of the respondents (59%) had positive behaviors including having children without diarrhea. Based on chi-square data processing with P value = 0.001 <0.05 this shows there is a meaningful relationship between parental behavioral variable with the incidence of diarrhea in infants. The results of this study are expected to increase knowledge, insight and understanding of the importance of how to prevent diarrhea in infants and apply Clean and Healthy Behavior (PHBS) in the household. Key Word : Behavior, Parents, Diarrhea in Toddlers